2008
DOI: 10.1016/j.jasms.2008.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography/mass spectrometry characterization of Escherichia coli and Shigella species

Abstract: Liquid© chromatography/quadrupole© time© of© flight© mass© spectrometry© (LC/QTOF© MS)© utilizing© electrospray© ionization© was© employed© to© monitor© protein© expression© in© Escherichia coli and Shigella organisms.© Comparison© with© MALDI/TOF-MS© revealed© more© proteins,© particularly above© 15© kDa.© A© combination© of© automated© charge© state© deconvolution,© spectral© mirroring, and© spectral© subtraction© was© used© to© reveal© subtle© differences© in© the© LC/MS© data.© Reproducible©intact©protein©… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 20 publications
1
27
1
Order By: Relevance
“…Furthermore, even though specialized mass spectrometry combined with liquid chromatography or affinity probes was shown to have the potential to differentiate between S. flexneri or S. sonnei and E. coli species, these techniques will require further development and validation to be applicable in routine clinical laboratory settings (31,32). Our study demonstrated that MALDI-TOF MS, using a routine sample preparation combined with a specialized and yet automated data analysis approach, can overcome existing analysis limitations.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, even though specialized mass spectrometry combined with liquid chromatography or affinity probes was shown to have the potential to differentiate between S. flexneri or S. sonnei and E. coli species, these techniques will require further development and validation to be applicable in routine clinical laboratory settings (31,32). Our study demonstrated that MALDI-TOF MS, using a routine sample preparation combined with a specialized and yet automated data analysis approach, can overcome existing analysis limitations.…”
Section: Discussionmentioning
confidence: 91%
“…Although other MS techniques, such as LC-MS, have also been used for microbial identification [24], MALDI-TOF MS has been adopted for routine diagnostics primarily because of the simplicity of sample preparation. However, a number of years passed before MALDI-TOF MS-based identification was considered suitable for routine use in clinical microbiology laboratories.…”
Section: Traditional Methods and Emerging Technologies For Bacterial mentioning
confidence: 99%
“…A known amount of a standard of known retention time can correct the shifts and serve as a standard to establish relative peak intensity [72]. The coupling of protein/ peptide separation by LC with ESI-MS analysis has one essential benefit over the routine MALDI-TOF-MS, proteins with equal masses can present different retention times in the LC and then, can be differentiated.…”
Section: Electrospray Ionization Mass Spectrometry (Esi-ms)mentioning
confidence: 99%
“…The coupling of protein/ peptide separation by LC with ESI-MS analysis has one essential benefit over the routine MALDI-TOF-MS, proteins with equal masses can present different retention times in the LC and then, can be differentiated. The strength of a coupled LC-ESI-MS access was demonstrated by Everley and colleagues that apply LC-QqTOF-MS to identify biomarkers for nonpathogenic E. coli, O157 EHEC and non-O157 EHEC as well as for Shigella flexneri and Shigella sonnei [53,72]. Disadvantages of ESI-MS involve low tolerance to contaminants in the sample and enhanced complexity of the mass spectra due to the presence of multiple charge states.…”
Section: Electrospray Ionization Mass Spectrometry (Esi-ms)mentioning
confidence: 99%